Ultra-long-toss vs Straight-line Throwing for Glenohumeral Range of Motion Recovery in Collegiate Baseball Pitchers. Issue 7 (21st July 2017) - Luo, Tianyi D.; Naugher, Gregory Lane; Stone, Austin; Mannava, Sandeep; Strahm, Jeff; Freehill, Michael T.
Objectives: Repetitive throwing in baseball pitchers can lead to pathologic changes in shoulder anatomy with potential subsequent injury. There have been few studies on throwing regimens and the types of throwing most efficacious for both maintenance and recovery during the baseball season. Limited-distance straight-line throwing (SLT) mimics more normal pitching mechanics, whereas ultra-long-toss (ULT) at greater than physiological throwing distances changes shoulder kinematics, but theoretically offers the advantage of stretching the posterior capsule. Debate exists as to whether ULT or SLT is superior for glenohumeral range of motion (ROM) recovery after baseball pitching. We hypothesize that ULT, via a potential mechanism of posterior shoulder capsular stretching, will be more effective in returning a pitcher's baseline external rotation (ER), internal rotation (IR), and total range of motion (TROM) when compared to SLT in a cohort of collegiate pitchers. Methods: Sixteen Division-I collegiate baseball pitchers were randomized to ULT (n=8, mean age 20.1 ± 1.4 years) or SLT group (n=8, mean age 20.0 ± 1.1 years). Measurements (dominant and non-dominant ER, IR, and TROM) were taken at five time-points across three days: before and immediately after a standardized bullpen (BP) session on day 1; before and immediately after a standardized ULT or SLT session on day 2; and before practice on day 3. Data were analyzed using mix design ANOVA. Post hoc analysis was used to detect differences between time-points. Results: In the ULT group (Table 1), dominant ER significantly increased from baseline to final measurements (129° to 136°, p=0.006). Significant increase in ER was observed between pre- and post-long-toss throwing (+6.2°, p=0.004). Dominant IR significantly decreased from baseline to final measurements (57° to 50°, p=0.002). TROM did not significantly change across time-points. In the SLT group, dominant ER increased from baseline to final measurements (139° to 142°), but failed to reach statistical significance. Dominant IR did not vary significantly across time-points, nor did TROM. Conclusion: Our results do not support our initial hypothesis. ULT yielded greater increases in ER and decreases in IR in comparison to SLT. Total range of motion did not change over time in either throwing group; however, the overall arc of motion changed more significantly in ULT pitchers, secondary to the greater ER and less IR. We had anticipated an increase in IR with ULT due to the theoretical advantage of posterior capsule stretching. The observed IR decrease suggests ULT may cause additive microtrauma resulting in capsular tightness rather than recovering shoulder ROM. Ultra-long-toss throwing should be further evaluated in the context of training, rehabilitation, and injury-prevention. Table 1. Dominant shoulder ROM in the ultra-long-toss group (n=8). Time-point ER IR TROM GIRD 1. Pre-BP 129.4 56.7 186 12.8 2. Post-BP 133.7 57.8 191.5 7.0 3. Pre-throw 131.6 49.2 180.8 15.1 4. Post-throw 137.8 52.4 190.2 14.5 5. Final 135.9 50.2 186.1 9.8 p-value <0.001 <0.001 <0.001 0.006